The implementation of “integration of sports and medicine” in China: Its limitation and recommendations for model improvement - Zhang, Ting; Ning, Zhihao; Dong, Li; Gao, Song (Frontiers in Public Health, 2022)
The “integration of exercise and medicine” (IEM) under the “Healthy China 2030” strategy can alleviate the contradiction between residents’ health needs and medical supply. Under the “Healthy China 2030” strategy, the government-initiated calls and measures for the integration of sports and medical institutions based on the actual region conditions. This article outlines the “Exercise-Medical Integration” program implemented in the coastal cities of China’s southeast, Suzhou and Shanghai. We described the specific implementation modes and related deficiencies of the IEM, taking Suzhou and Shanghai as examples. Through three policy recommendations, we put forward the idea of promoting the development of a new model of IEM in China.